2021
DOI: 10.1111/anu.13412
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of dietary l ‐carnitine and ractopamine supplementation on growth and nutritional composition of Labeo calbasu (Hamilton, 1822)

Abstract: Fish is an important constituent of human diet and are known to be the less expensive source of animal protein apart from a rich source of micro and macro minerals and other nutrients (Andrew, 2001;Mazumdar & Basu, 2009). The cost of feed is one of the major concerns for the success of fish culture. Hence, the formulation of a cost-effective feed with better conversion ratio is of utmost importance. Increase in dietary fat content in the fish feed induces the protein-sparing effect and enhances the utilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Mustin and Lovell [14] observed positive effects of ractopamine on younger channel catfish, while Bicudo et al [20] found similar results in pacu (Piaractus mesopotamicus) fingerlings. Vandenberg et al [10] and Singh et al [23] observed that rainbow trout juveniles and calbasu also exhibited similar trends. The present study revealed that feeding all-female prawns with a diet containing the betaagonist RAC resulted in a substantial growth increase at a dosage of 10 mg/kg of feed.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Mustin and Lovell [14] observed positive effects of ractopamine on younger channel catfish, while Bicudo et al [20] found similar results in pacu (Piaractus mesopotamicus) fingerlings. Vandenberg et al [10] and Singh et al [23] observed that rainbow trout juveniles and calbasu also exhibited similar trends. The present study revealed that feeding all-female prawns with a diet containing the betaagonist RAC resulted in a substantial growth increase at a dosage of 10 mg/kg of feed.…”
Section: Discussionmentioning
confidence: 84%
“…It may have an anabolic impact on protein metabolism, causing muscle fiber growth and frequent changes in muscle fiber type [12]. Ractopamine has been tested in a few species of fish, such as channel catfish [13,14], rainbow trout [15][16][17][18][19], pacu [20,21], Hungarian carp [22], tilapia [5], and calbasu [23], with both positive and contradictory results. The objective of this study was thus to evaluate the effect of ractopamine as a dietary additive on the growth performance and gonadal maturity of all-female prawns.…”
Section: Introductionmentioning
confidence: 99%
“…Among the bene ts of these fatty acids on human health, there is an increase in insulin sensitivity and consequent reduction in blood glucose; decreased risk of metabolic syndrome; and lowering blood pressure (Santos et al 2013). An increase in the amount of MUFA in body composition was also demonstrated when Labeo calbasu ngerlings were fed a diet containing 1 g kg − 1 of L-canitine and 10 mg kg − 1 of RAC (Singh et al 2021).…”
Section: Discussionmentioning
confidence: 77%
“…Salem et al (2006) observed that rainbow trout fed with diets containing RAC showed changes in RNA production resulted in the increased expression of genes MHC-f and β-actin, which suggests anabolic effects for higher protein depositions on muscle myo brils. Supplementation with RAC and L-carnitine also promoted muscle growth in Labeo calbasu (Singh et al 2021).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation